Lithuanian railways marked on old maps - Lukoševičius, Viktoras (Geodesy and Cartography, 2012)
This paper researches the representation of Lithuanian railways as a geographical object on old maps. It highlights the most significant stages of development of wide and narrow gauge railways and that of cartography in the background of historical events. The paper presents maps of Lithuanian railways collected from different sources and discusses map characteristics. It also provides links that are helpful to readers interested in more detailed studies of specific maps. The author summarises the research results by making a conclusion that old maps are an excellent source for historic studies of the development of Lithuanian state transport system and its impact on local and foreign economy. The author expects that the material presented in the paper will acquaint its readers with Lithuanian railway maps and become an object of research for those who are interested in the past of the nation and the state. The author stresses the ultimate necessity to reconstruct the map depicting the old internal network of Lithuanian railways in order to conserve these historic documents that are important to the Lithuanian state. This would allow a wider public access to them versus a small group of researchers of history archives. Article in Lithuanian. Lietuvos geležinkeliai senuosiuose žemėlapiuose Lithuanian railways marked on old maps Santrauka. Tęsiant senosios kartografijos tyrinėjimus (Girkus, Lukoševičius 2011) norima pažvelgti į vieno iš geografinių objektų – Lietuvos geležinkelių vaizdavimą žemėlapiuose istorinių įvykių perspektyvoje, išskirti reikšmingiausius plačiųjų ir siaurųjų geležinkelių raidos etapus ir kartografijos plėtotės momentus. Pristatomi iš įvairių šaltinių surinkti Lietuvos geležinkelių žemėlapiai ir jų charakteristikos. Pateikiamos nuorodos norimam žemėlapiui rasti išsamesnėms studijoms. Apibendrinant tyrimo rezultatus daroma išvada, kad senoviniai žemėlapiai yra puikūs istorijos liudytojai, padedantys suvokti turtingą ir įdomų Lietuvos valstybės transporto sistemos formavimosi procesą ir reikšmę vidaus bei tarptautinei ekonomikai. Pateikiama medžiaga – įdomi bei naudinga pažintis su praeitį liudijančiais Lietuvos geležinkelių žemėlapiais ir kartu tyrimo objektas kiekvienam, besidominčiam savo tautos ir valstybės praeitimi. Reikšminiai žodžiai: Lietuva, istoriografija, žemėlapiai, platusis geležinkelis, siaurasis geležinkelis, vietovardžiai.